2010
DOI: 10.1073/pnas.0913125107
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length is inherited with resetting of the telomere set-point

Abstract: We have studied models of telomerase haploinsufficiency in humans and mice to analyze regulation of telomere length and the significance of "set points" in inheritance of telomere length. In three families with clinical syndromes associated with short telomeres resulting from haploinsufficient mutations in TERT, the gene encoding telomerase reverse transcriptase, we asked whether restoration of normal genotypes in offspring of affected individuals would elongate inherited short telomeres. Telomeres were shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
56
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 32 publications
6
56
0
Order By: Relevance
“…Therefore, this indicates that a subject's TL at least partially reflects the TL of his/her parents' specific germ cells. Note that this direct mechanism, which is also supported by studies in mice, 9 is indeed straightforward and has been suggested before by us and others. 8,10 However, it is an unlikely mechanism in case of X-linked or paternal inheritance.…”
supporting
confidence: 86%
“…Therefore, this indicates that a subject's TL at least partially reflects the TL of his/her parents' specific germ cells. Note that this direct mechanism, which is also supported by studies in mice, 9 is indeed straightforward and has been suggested before by us and others. 8,10 However, it is an unlikely mechanism in case of X-linked or paternal inheritance.…”
supporting
confidence: 86%
“…However, in the latter case, we acknowledge that although the differences observed at the two-cell stage are only dependent on spermatozoa TL, the differences observed later, after the onset of embryonic telomerase expression, may have been influenced by possible differences in activity or expression between Mus musculus and Mus spretus telomerases. Further support for the major role of spermatozoa TL in offspring TL comes from a study of TERT haploinsufficiency in mice, where the restoration of TERT was not able to restore TL in the offspring, thereby suggesting that other factors, such as sperm TL, determined the offspring TL (Chiang et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…We could hypothesize that the pattern of telomere length heredity is dependent on the inheritance pattern of multiple telomere length restoration/maintenance factors (Blackburn, 2001;Blasco, 2007b). A resetting mechanism of early-life telomere length has been pointed out in mammals, in which both telomerase activity and parent telomere length are interacting to set-up the embryo starting telomere length (Chiang et al, 2010). Focusing on these processes in the future might enable us to better understand how progressive telomere shortening over generations is avoided and how interspecific variability in telomere dynamics may have evolved.…”
Section: Discussionmentioning
confidence: 99%